Resenha do livro Contested territory: mapping Peru in the sixteenth and seventeenth centuries, de Heidi V. Scott - Vigneron de La Jousselandière, Victor Santos (Anos 90, 2013)
Resenha do livro Contested territory: mapping Peru in the sixteenth and seventeenth centuries, de Heidi V. Scott.